PENGARUH DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SMA NEGERI 1 TELUK KUANTAN - Ativa Sakhara Fitri; Suarman Suarman; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the significant influence of learning discipline on student learning achievement in the Economics Subject of SMA Negeri 1 Teluk Kuantan. This research uses descriptive quantitative method and the population in this study is the 11th grade social studies students totaling 110 people and the sample is obtained by using proportional random sampling technique as many as 52 respondents. Data analysis techniques used were descriptive analysis, Simple Linear Regression, hypothesis testing, and determination coefficient (R2) with the help of SPSS version 16.0. and seen the F test is known to count F (40,100)> F table (4,034) with Sig (0,000) <0,05. Thus the hypothesis is answered that the discipline learning variable (X) simultaneously has a significant effect on student learning achievement (Y). The simple linear regression equation obtained in this study is Y = 34.993 + 0.348 X. This means that if the discipline learning variable is assumed to be zero (0), then the learning achievement is 34.993. The value of regression coefficient variable learning discipline of 0.348. The meaning is that every increase in learning discipline by 1 unit will increase learning achievement by 0.348 and vice versa. The results of the research on the determination coefficient (R2) showed that the percentage of contribution to the contribution of learning discipline variables to learning achievement was 44.5%. and the rest as much as the remaining 55.5% is influenced by other variables not explained in this study. For this reason, it is necessary to improve by approaching both the teacher and the school teacher so that a good learning discipline can be realized in the teaching and learning process in order to improve satisfactory learning achievement.Key Words: Discipline Learning, Learning Achievement